2020
DOI: 10.1007/s11104-020-04483-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rising body weight and cereal grain food processing on human magnesium nutrition

Abstract: Aim The World Health Organisation (WHO) magnesium (Mg) estimated average requirement (EAR) is not adjusted for rise in human body weight (BW) and neglects body Mg stores depletion. Cereal grain food processing results in Mg loss and reduces dietary Mg intake which mainly originates from cereals. Here we reassess human dietary Mg deficiency risk considering actual human BWs and modern levels of cereal grain food processing. Methods Human Mg requirement was adjusted for rising BW plus low and high estimates to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Approximately two-thirds of adults in western countries do not consume satisfactory amounts of Mg, resulting in the nutritional disorder called “hypomagnesemia” that subsequently escalates to chronic diseases from its hidden deficiency (Hermans et al, 2013 ). The Mg-related nutritional disorders in humans are linked to declining Mg concentrations in the soil and food crops (Rosanoff, 2013 ; Rosanoff and Kumssa, 2020 ). Therefore, optimizing Mg nutrition is an imperative concern for food security and human health (Broadley and White, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two-thirds of adults in western countries do not consume satisfactory amounts of Mg, resulting in the nutritional disorder called “hypomagnesemia” that subsequently escalates to chronic diseases from its hidden deficiency (Hermans et al, 2013 ). The Mg-related nutritional disorders in humans are linked to declining Mg concentrations in the soil and food crops (Rosanoff, 2013 ; Rosanoff and Kumssa, 2020 ). Therefore, optimizing Mg nutrition is an imperative concern for food security and human health (Broadley and White, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Homeostatic control of serum K concentration occurs mainly through the regulation of urinary K excretion. However, reduced dietary intake of Mg [ 12 ] and K [ 2 ], and increased consumption of Na [ 13 , 14 ] due to food processing and high intake of salt [ 15 ] affect the utilisation of K. Loss of K during food processing reduces dietary K intake [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of K deficiency in populations with median K supply greater or equal to the AI is likely to be low; however, the inverse cannot be assumed where the median K intake is less than the AI [ 21 ], and this limits the ability to assess the adequacy of population K intakes. This contrasts with other mineral micronutrients which have RDAs and Estimated Average Requirement (EAR) values defined, from which the prevalence of inadequate dietary intakes and risk of deficiency can be estimated [ 9 , 12 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fact is important because a deficient intake of Mg is related to cardiovascular diseases, type 2 diabetes, etc. [ 30 ]. Studies carried out by Laskowski et al [ 31 ] showed that cereals are the main source of Mg in the diet.…”
Section: Resultsmentioning
confidence: 99%